A conceptual framework for predicting and addressing the consequences of disease‐related microvascular dysfunction. (August 2017) - McClatchey, Penn M.; Frisbee, Jefferson C.; Reusch, Jane E. B.
Abstract: Objective: A growing body of evidence indicates that impaired microvascular perfusion plays a pathological role in a number of diseases. This manuscript aims to better define which aspects of microvascular perfusion are important, what mass transport processes (eg, insulin action, tissue oxygenation) may be impacted, and what therapies might reverse these pathologies. Methods: We derive a theory of microvascular perfusion and solute flux drawing from established relationships in mass transport and anatomy. We then apply this theory to predict relationships between microvascular perfusion parameters and microvascular solute flux. Results: For convection‐limited exchange processes (eg, pulmonary oxygen uptake), our model predicts that bulk blood flow is of primary importance. For diffusion‐limited exchange processes (eg, insulin action), our model predicts that perfused capillary density is of primary importance. For convection/diffusion co‐limited exchange processes (eg, tissue oxygenation), our model predicts that various microvascular perfusion parameters interact in a complex, context‐specific manner. We further show that our model can predict established mass transport defects in disease (eg, insulin resistance in diabetes). Conclusions: The contributions of microvascular perfusion parameters to tissue‐level solute flux can be described using a minimal mathematical model. Our results hold promise for informing therapeutic interventions targeting microvascular perfusion.